Culture potential and population structure of the indigenous oysters Striostrea margaritacea and Saccostrea cucullata in South Africa - Keightley, Jenna (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.